EXAMINING THE WORTHINESS OF THE ART TEXTBOOK BASED ON THE LOCAL WISDOM IN KABUPATEN JOMBANG (THE RELEVANCE IN STRENGTHENING THE CHARACTERS OF PRIMARY TEACHER EDUCATION STUDENTS AT HASYIM ASY'ARI UNIVERSITY TEBUIRENG JOMBANG) - Ratih Asmarani; Novia Dwi Rahmawati; Sri Widoyoningrum (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
The development of learning resources, such as art textbooks based on local wisdom in Kabupaten Jombang, was carried out by referring to the Borg and Gall model. The feasibility of these textbooks was examined by media experts, material experts, and students. This study aimed to investigate the feasibility of art textbooks based on local wisdom in Kabupaten Jombang from various expert perspectives. A descriptive qualitative research method was employed. Data were collected through participatory observation and field trials to determine the usefulness of the product. The data from expert validations and student trials were analyzed using the Likert scale criteria. The total scores were converted into percentages and then interpreted qualitatively using product feasibility guidelines. The results showed that the average score from material experts was 77%, from media experts was 95%, and from the large group student trial was 85.3%. The overall average score was 86.47%, indicating that the product was categorized as very suitable to be used as a primary learning resource.